2016
DOI: 10.1016/j.molp.2016.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Rubisco Activity by Non-enzymatic Acetylation of RbcL

Abstract: Atmospheric carbon dioxide (CO2) is assimilated by the most abundant but sluggish enzyme, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco). Here we show that acetylation of lysine residues of the Rubisco large subunit (RbcL), including Lys201 and Lys334 in the active sites, may be an important mechanism in the regulation of Rubisco activities. It is well known that Lys201 reacts with CO2 for carbamylation, a prerequisite for both carboxylase and oxygenase activities of Rubisco, and Lys334 contacts wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
70
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 39 publications
2
70
2
Order By: Relevance
“…Hence, determination of which protein acetyltransferases modify these various proteins remains to be investigated in future studies. In addition to the enzyme-catalyzed acetylation, nonenzymatic acetylation can also result in lysine modification [50], which plays different roles according to different species [51,52]. In E .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, determination of which protein acetyltransferases modify these various proteins remains to be investigated in future studies. In addition to the enzyme-catalyzed acetylation, nonenzymatic acetylation can also result in lysine modification [50], which plays different roles according to different species [51,52]. In E .…”
Section: Resultsmentioning
confidence: 99%
“…For example, ribulose-1,5-bisphosphate carboxylase/oxygenase (Rubisco), the key carbon fixation enzyme, was crotonylated at 15 amino acid sites. The key amino acid residues of Rubisco, K201 and K334 which were identified as acetylated resulting in the downregulation of Rubisco activity 47 , also modified through crotonylation. This result suggested that crotonylation might change Rubisco activity in coordination with acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…While the effects of phosphorylation on Rca activity are not known yet, this suggests a potential method of regulation for carbon reduction enzymes in addition to the thioredoxin-mediated regulation discussed above. Other posttranslational regulatory mechanisms directly affect Rubisco (Houtz et al, 2008), such as acetylation (Gao et al, 2016), but their effects in dynamic light have yet to be examined. As more of the key players are identified and the mechanisms by which they regulate carbon metabolism in rapidly changing light conditions are elucidated, they will likely be used to enhance the responsiveness of carbon reduction enzymes in fluctuating light.…”
Section: The Control Of Carbon Reduction Enzymes In the Face Of Stop-mentioning
confidence: 99%